Self-powered forest fire alarm system based on impedance matching effect between triboelectric nanogenerator and thermosensitive sensor. (July 2020) - Liu, Wenquan; Wang, Xin; Song, Yongxin; Cao, Ruirui; Wang, Liangliang; Yan, Zhengguang; Shan, Guiye
Abstract: As worldwide forest fire frequently causes a serious threat to forest resources and global climate change, novel early forest fire monitoring and detection technologies are urgently required to explore. Herein, a self-powered forest fire alarm system (FFAS) is proposed by coupling thermosensitive effect and triboelectric effect as an aim of effective forest fire monitoring and detecting. The FFAS is fabricated as a self-powered early forest fire monitoring and detection system by connecting a spherical free-standingmode triboelectric nanogenerator (S-TENG) as power source with polydopamine-modified graphene oxide (P-GO) as thermosensitive sensor and commercial LEDs as alarm. When encountering an open fire or abnormal high temperature the thermosensitive sensor based on P-GO can be in-situ thermally reduced, inducing an obvious transition in electrical resistance. Thus, the output voltage of S-TENG can be tuned by the impedance matching effect between special output characteristics of TENG and working status of thermosensitive sensor, and then can directly light up the LEDs as alarm. Furthermore, the FFAS achieves a low temperature response (160 °C), rapid response time (~3 s), and especially no external power supply. Consequently, the FFAS based on impedance matching effect between TENG and thermosensitive sensor would provide a real-time, rapidly responsive, and self-powered monitoring strategy for the early forest fire warning and detection. Graphical abstract: A self-powered forest fire alarm system (FFAS) was proposed based on impedance matching effect between TENG and thermosensitive sensor. When encountering an open fire the P-GO thermosensitive sensor can be reduced to decrease dramatically the electrical resistance. Thus, the output voltage of TENG driven by natural wind can be tuned to directly light up the LEDs as alarm. The response time (3 s) for the resistance change is consistent with that of the output voltage profile in open fire. The self-powered FFAS based on TENG would provide a novel strategy for a real-time, rapid response, and self-powered early forest fire monitoring and detection. Image 1 Highlights: A self-powered forest fire alarm system is demonstrated based on an impedance matching effect between TENG and P-GO sensor. The electric resistance of P-GO was decreased dramatically when encountering open fire or high temperature more than 160 °C. The response time (3 s) of resistance change is consistent with that of output voltage performance of TENG under open fire. The low temperature response (160 °C) and rapid response time (3 s) endow the self-powered FFAS for forest fire monitoring.